The Controversy of the Death Penalty for Narcotics Dealers: A Review of Indonesian Criminal Law and Islamic Criminal Law - Harefa, Safaruddin (Istinbath : Jurnal Hukum, 2025)
This study explores the application of the death penalty to narcotics traffickers within the frameworks of Indonesian national criminal law and Islamic criminal law. Under Law Number 35 of 2009 concerning Narcotics, the death penalty is imposed as a sanction for severe drug-related offences. In Islamic criminal law, punishment falls under ta’zir, which allows the state to impose discretionary penalties based on the gravity of the harm caused and the need to protect public welfare. Fatwas issued by the Indonesian Ulema Council (MUI) and the Council of Senior Scholars in Saudi Arabia affirm that capital punishment may be implemented under ta’zir to combat the growing threat of drug trafficking. This research aims to examine the legal foundation and implications of the death penalty in both legal systems, with an emphasis on justice, deterrence, and social protection. The study employs a normative juridical method and a comparative approach, analysing statutory laws and Islamic legal doctrines. Findings reveal that while both systems permit the death penalty, its application must consider broader dimensions such as prevention, rehabilitation, and social consequences. The study concludes that the death penalty, when implemented prudently and within the scope of legal and ethical standards, can function as a strategic instrument to address narcotics trafficking. The death penalty should not be viewed merely as a form of retribution, but rather as a comprehensive legal response aimed at preserving social order and public health.